Pengaruh Garansi, Promosi dan Kualitas Produk Terhadap Keputusan Pembelian Produk Moorlife di Kota Jambi - Agesha Marsyaf (J-MAS (Jurnal Manajemen dan Sains), 2021)
Most Indonesians bringing food or drink has become a habit. Bringing provisions is currently positive for the development of household appliance manufacturers made of plastic, this is because its practical use, not easily broken, its attractive design and color make the reason why plastic products are loved by the community, one of which is Moorlife products from year to year experiencing a significant increase in sales. This research aims to find out partially and simultaneously the influence of promotion, warranty, and product quality on moorlife product purchase decisions in Jambi City. The method used is quantitative method. The data used is primary data obtained from in-person interviews and using questionnaires. The results showed that the Promotion, Warranty and Quality of Products had a positive and significant effect on the decision of consumers to buy Moorlife Products in jambi City. And overall Promotion, Warranty and Product Quality contributed 46.4% to Moorlife Products in Jambi City.